Oligopolistic Reaction and Foreign Direct Investment: The Case of the U.S. Tire and Textiles Industries - Yu, Chwo-Ming J.; Ito, Kiyohiko (Journal of International Business Studies, 1988)
This paper empirically tests the impact of oligopolistic reaction and some firm–related and host country–related factors on FDI activities in the U.S. tire and textile industries. The results reveal that in an oligopolistic industry, firms' motivation of FDI is based on the behavior of rivals as well as host country–related and firm–related factors, while in a more competitively structured industry, firms do not actively counter the competitors' FDI activities.